Pengaruh Good Corporate Governance dan Investment Opportunity Set terhadap Kebijakan Dividen - Kadek Apriada; Putu Riska Wulandari (Jurnal Inovasi Akuntansi (JIA), 2024)
Good Corporate Governance (GCG) is a guarantee that comes from the control system in a company which can be seen from the procedures of the independent board of commissioners (DKI), institutional ownership (KI), managerial ownership (KM), and audit committee (KA). Good governance can indicate that the company is able to ensure good management of the company's finances. Investment Opportunity Set is the value of the company which depends on the costs set by management for the future. If a company has many profitable investment opportunities, this will likely lead to a low dividend payout ratio. The population of this study was 84 food and beverage companies registered on the IDX. The sampling technique used was purposive sampling. The analysis technique used in this research is multiple linear regression. The results of this research show that managerial ownership, institutional ownership, audit committee, and investment opportunity set have a positive effect on dividend policy. Meanwhile, the board of commissioners has a negative influence on dividend policy. Further research can develop this research by using other variables which theoretically have an influence on dividend policy